Solid ion source based on hollow-cylindrical magnetron sputtering discharge - Azarenkov, N.A.; Bizyukov, A.A.; Bizyukov, I.A.; Bobkov, V.V.; Kashaba, A.E.; Krieger, K.; Sereda, K.N.; Tarasov, I.K. (Вопросы атомной науки и техники, 2003)
A new solid ion source is described. The ion source based on hollow-cylindrical magnetron sputtering discharge produces the beam of various solid ions (B, C, Si, Ti, V, Fe, Ni, Ta, W) which are then extracted by an ion optical accelerating system. In this ion source DC discharge is used for generation of the ions of different metals and capacitively coupled RF discharge with a frequency 13.56 MHz is used for generation of the ions of other solid materials. Описано нове джерело твердотільних іонів. Джерело іонів на базі порожнього циліндричного розпилюючого магнетронного розряду генерує пучок різних твердотільних іонів (B, C, Si, Ti, V, Fe, Ni, Ta, W), які потім витягаються іонно-оптичною прискорюючою системою. У цьому іонному джерелі для генерації іонів різних металів використовується розряд постійного струму, а для генерації іонів інших твердих матеріалів використовується ємнісний ВЧ-розряд з частотою 13,56 Мгц. Описан новый источник твердотельных ионов. Источник ионов на базе полого цилиндрического распылительного магнетронного разряда производит пучок различных твердотельных ионов (B, C, Si, Ti, V, Fe, Ni, Ta, W), которые затем извлекаются ионно-оптической ускорительной системой. В этом ионном источнике для генерации ионов различных металлов используется разряд постоянного тока, а для генерации ионов других твердых материалов используется емкостной ВЧ-разряд с частотой 13,56 МГц.